Composite Materials Engineering, Volume 2 Different Types of Composite Materials (Springer Singapore, 2018)
In two volumes, this book provides comprehensive coverage of the fundamental knowledge and technology of composite materials. This second volume reviews the research developments of a number of widely studied composite materials with different matrices. It also describes the related process technology that is necessary for a successful production. This work is ideal for graduate students, researchers, and professionals in the fields of materials science and engineering, as well as mechanical engineering.